Insomnia and hypersomnia in major depressive episode: Prevalence, sociodemographic characteristics and psychiatric comorbidity in a population-based study - Geoffroy, Pierre A.; Hoertel, Nicolas; Etain, Bruno; Bellivier, Frank; Delorme, Richard; Limosin, Frédéric; Peyre, Hugo (Journal of affective disorders, 2018)
To examine (i) the frequency of different sleep complaints (early wake-up, trouble falling asleep, hypersomnia) and their co-occurrence and (ii) the sociodemographic characteristics and psychiatric comorbidity associated with each type of sleep profiles. Data were drawn from the Wave 2 National Epidemiologic Survey on Alcohol and Related Conditions, a nationally representative survey of the US adult population (wave 1, 2001–2002; wave 2, 2004–2005). The primary analyses were limited to 3573 participants who had a DSM-IV-TR diagnosis of major depressive episode (MDE) between the two waves. We used a multiple regression model to estimate the strength of independent associations between self-reported sleep complaints, sociodemographic characteristics and lifetime psychiatric comorbidity. Most of participants with MDE (92%) reported significant sleep complaints, from whom 85.2% had insomnia and 47.5% hypersomnia symptoms. The prevalence rates were for insomnia “only” of 48.5%, hypersomnia “only” of 13.7%, and their co-occurrence of 30.2%. We found that several sociodemographic characteristics (gender, age, education, individual and familial income, marital status) and psychiatric disorders (bipolar disorders, post-traumatic disorders and panic disorder) were significantly and independently associated with different sleep profiles. The co-occurrence of insomnia (especially early wake-up) and hypersomnia presented with a two-/three- fold increase risk of bipolar disorders. Definitions of sleep complaints were qualitative and subjective. Sleep complaints are prevalent and heterogeneous in expression during MDE. Sleep disturbance profiles are associated with specific patterns of comorbidity. Our findings highlight the importance of continued research on sleep complaints during MDE while taking into account psychiatric comorbidity. •More than 90% of patients with MDE suffer from sleep complaints.•Insomnia is the complaint the most frequently reported in MDE (~85%),•Hypersomnia is also frequent and is present in ~50% of MDE.•Up to one-third of MDE reported both insomnia and hypersomnia.•Co-occurrence of sleep complaints is associated with BD, PTSD and panic disorder.